2023
DOI: 10.1021/acsomega.2c06508
|View full text |Cite
|
Sign up to set email alerts
|

Concentration-Dependent Cellular Uptake of Graphene Oxide Quantum Dots Promotes the Odontoblastic Differentiation of Dental Pulp Cells via the AMPK/mTOR Pathway

Abstract: As zero-dimension nanoparticles, graphene oxide quantum dots (GOQDs) have broad potential for regulating cell proliferation and differentiation. However, such regulation of dental pulp cells (DPSCs) with different concentrations of GOQDs is insufficiently investigated, especially on the molecular mechanism. The purpose of this study was to explore the effect and molecular mechanism of GOQDs on the odontoblastic differentiation of DPSCs and to provide a theoretical basis for the repair of pulp vitality by pulp … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Alizarin red staining revealed that compared to CM-EV and the control group, OM-EV substantially incorporated into the formation growth of mineralized nodules, particularly on day 14. The ALP is commonly regarded as an early marker of odontogenic differentiation and is noticeably expressed after one week of induction [ 21 , 34 , 35 ]. Therefore, we performed ALP staining and ALP activity detection only on day 7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alizarin red staining revealed that compared to CM-EV and the control group, OM-EV substantially incorporated into the formation growth of mineralized nodules, particularly on day 14. The ALP is commonly regarded as an early marker of odontogenic differentiation and is noticeably expressed after one week of induction [ 21 , 34 , 35 ]. Therefore, we performed ALP staining and ALP activity detection only on day 7.…”
Section: Discussionmentioning
confidence: 99%
“…A series of studies have revealed that the promotion of odontoblast differentiation by EVs from dental mesenchymal stem cells may be achieved through regulating multiple signaling pathways (such as Wnt/β-catenin [ 32 ], p38/MAPK [ 13 ], and TGF-β/smads [ 15 ]) by microRNA, and proteins were carried by EVs. In a previous article by our team, we also suggested the correlation between the AMPK/mTOR pathway and the odontogenic differentiation of DPSCs [ 21 ]. The obtained results of pathway analysis and Western blotting revealed that the activation of the AMPK/mTOR pathway may play a pivotal role in regulating the odontogenic differentiation of DPSCs by OM-EV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After 14-day odontoblastic differentiation, the expression level of phosphorylated AMPK increased, while the expression level of phosphorylated mTOR decreased. This indicated that GOQDs would activate the AMPK signaling pathways but inhibit the mTOR signaling pathways in DPSCs (Lin et al, 2023). Xu et al (2021) found that NaF promoted osteo/odontogenic differentiation of DPSCs by suppressing the PI3K/AKT/mTOR signaling pathways.…”
Section: Phosphoinositide-3-kinase/protein Kinase B/mammalian Target ...mentioning
confidence: 97%